2017
DOI: 10.1124/mol.116.106583
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Activation Promotes α1B-Adrenoceptor Internalization and Late Endosome Trafficking through Rab9 Interaction. Role in Heterologous Desensitization

Abstract: Upon agonist stimulation, -adrenergic receptors couple to G proteins, calcium signaling and protein kinase C activation; subsequently, the receptors are phosphorylated, desensitized, and internalized. Internalization seems to involve scaffolding proteins, such as -arrestin and clathrin. However, the fine mechanisms that participate remain unsolved. The roles of protein kinase C and the small GTPase, Rab9, in-AR vesicular traffic were investigated by studying -adrenergic receptor-Rab protein interactions, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
(103 reference statements)
1
14
0
Order By: Relevance
“…This may explain our finding that the PKC-induced β-arrestin2 recruitment directed the receptor to Rab7-enriched late endosomes to a lesser extent than AngII. Interestingly, the heterologous β-arrestin2 recruitment to α 1B-adrenergic receptor was shown to promote late endosomal trafficking, indicating that this type of regulation exhibits receptor specificity (59). Additionally, in a previous study we showed that the intracellular fate of AT1R is ligand-specific (48).…”
Section: O N F I D E N T I a L Heterologous Regulation Of Inactive mentioning
confidence: 88%
“…This may explain our finding that the PKC-induced β-arrestin2 recruitment directed the receptor to Rab7-enriched late endosomes to a lesser extent than AngII. Interestingly, the heterologous β-arrestin2 recruitment to α 1B-adrenergic receptor was shown to promote late endosomal trafficking, indicating that this type of regulation exhibits receptor specificity (59). Additionally, in a previous study we showed that the intracellular fate of AT1R is ligand-specific (48).…”
Section: O N F I D E N T I a L Heterologous Regulation Of Inactive mentioning
confidence: 88%
“…Agonist‐activated α 1B ‐adrenoceptors (associated with homologous desensitization) mainly interacted with proteins present in early endosomes, such as early endosome antigen 1, Rab5, Rab4, and Rab11, but not with the late endosome markers Rab9 and Rab7 (Alfonzo‐Méndez et al, ; Castillo‐Badillo et al, ). In contrast, the activation of other receptors (such as sphingosine 1‐phosphate receptors) or direct activation of PKC by phorbol esters (heterologous desensitization) induced a brief α 1B ‐adrenoceptor–Rab5 interaction, a more pronounced and sustained one with Rab9, and some interaction with Rab7 (Alfonzo‐Méndez, Hernández‐Espinosa, et al, ; Castillo‐Badillo et al, ). It is worth mentioning that the action of sphingosine‐1‐phosphate on the phosphorylation/desensitization/internalization of α 1B ‐adrenoceptors mainly depended on the activation of PKC (Alfonzo‐Méndez, Hernández‐Espinosa, et al, ).…”
Section: Association Of α1‐adrenoceptors With Rab Proteinsmentioning
confidence: 99%
“…Monoclonal anti‐GFP antibody (cat number 632381) was purchased from Clonthech, while secondary antibodies were from Zymed (Thermo Fisher Scientific) or Jackson ImmunoResearch Laboratories (West Grove, PA, USA) and chemiluminescence kits were from Millipore Corporation (Merck‐Millipore). Other materials were obtained from previously published sources .…”
Section: Methodsmentioning
confidence: 99%
“…HEK 293 cells (American Type Culture Collection, Manassas, VA, USA) were cultured as described . These cells do not appear to express functional free fatty acid receptors but do express LPA 1 receptors .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation